2021
DOI: 10.1186/s12905-021-01543-7
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure and internal reliability of breast cancer screening Champion’s Health Belief Model Scale in Yemeni women in Malaysia: a cross-sectional study

Abstract: Background The reliability and validity of the Champion’s Health Belief Model Scale (CHBMS) used in assessing the belief of women regarding breast cancer (BC) and breast cancer screening (BCS) have been examined on various populations. However, the use of this tool has not been adequately assessed for its validity in ethnic minorities. This study assessed the validity and reliability of CHBMS by analyzing the factor structure and internal reliability of the factors among Yemeni women in Malaysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 50 publications
0
22
0
Order By: Relevance
“…The objective of this step is to obtain goodness of fit statistics, which include the p -value of the Chi-Square statistic (non-significant), the Bentler–Bonett normed fit index (NFI) (≥0.90), the Bentler–Bonett non-normed fit index (NNFI) (≥0.90), the comparative fit index (CFI) (≥0.90), Bollen’s incremental fit index (IFI) (≥0.90), the Joreskog–Sorbom goodness of fit index (GFI) (≥0.90), the root mean square residual (RMR) (≤0.08), the standardized root mean square residual (SRMR) (≤0.08), the root mean square error of approximation (RMSEA) (≤0.08), and the 90% confidence interval of RMSEA (90% CI RMSEA) (≤0.08) [ 66 , 68 , 72 , 82 , 83 , 90 , 91 , 93 , 94 , 95 ]. The researcher can check for the re-specified model if the original model is a misfit until the researcher holds the fit model.…”
Section: Methodsmentioning
confidence: 99%
“…The objective of this step is to obtain goodness of fit statistics, which include the p -value of the Chi-Square statistic (non-significant), the Bentler–Bonett normed fit index (NFI) (≥0.90), the Bentler–Bonett non-normed fit index (NNFI) (≥0.90), the comparative fit index (CFI) (≥0.90), Bollen’s incremental fit index (IFI) (≥0.90), the Joreskog–Sorbom goodness of fit index (GFI) (≥0.90), the root mean square residual (RMR) (≤0.08), the standardized root mean square residual (SRMR) (≤0.08), the root mean square error of approximation (RMSEA) (≤0.08), and the 90% confidence interval of RMSEA (90% CI RMSEA) (≤0.08) [ 66 , 68 , 72 , 82 , 83 , 90 , 91 , 93 , 94 , 95 ]. The researcher can check for the re-specified model if the original model is a misfit until the researcher holds the fit model.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have confirmed that some aspects of beliefs can be statistically analyzed in the form of numbers. 20–25 28 Many scholars developed questionnaires with numerical values based on the health belief model to measure an individual’s health beliefs about various diseases and health behaviors, such as oral health beliefs in adolescence, 25 popular beliefs about COVID-19 infection risks, 27 beliefs about colorectal cancer screening prevention, 20 and health beliefs about breast screening behaviors. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Moreover, SEM allows for simultaneously estimating a series, but independent, multiple regression equations cannot. It can also incorporate latent variables into the analysis and accounts for measurement errors in the estimation process [ 60 , 61 , 62 , 63 , 64 ]. In other words, SEM is a statistical technique that establishes measurement models and structural models to address complicated behavioral relationships [ 61 , 62 , 65 , 66 ].…”
Section: Methodsmentioning
confidence: 99%